2016
DOI: 10.5115/acb.2016.49.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Dorsoscapularis triangularis: embryological and phylogenetic characterization of a rare variation of trapezius

Abstract: The muscle trapezius shows considerable morphological diversity. Variations include an anomalous origin and complete or partial absence of the muscle. The present study reported, a hitherto undocumented complete bilateral absence of the cervical part of trapezius. Based on its peculiar origin and insertion, it was named dorsoscapularis triangularis. The embryological, phylogenetic and molecular basis of the anomaly was elucidated. Failure of cranial migration of the trapezius component of the branchial muscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Developmentally, this variant may have occurred due to aberrancies in the signaling of the Hox gene in the development of the myotome that gives rise to the SCM and trapezius, both seen to fuse at their respective insertions, and on occasion make contact with one another along their medial parts [4715]. Embryologically, these structures arise together as an aggregation of cells readily observed at Carnegie stage 15 (CS15), and are referred to as the trapezius/SCM muscle complex.…”
Section: Discussionmentioning
confidence: 99%
“…Developmentally, this variant may have occurred due to aberrancies in the signaling of the Hox gene in the development of the myotome that gives rise to the SCM and trapezius, both seen to fuse at their respective insertions, and on occasion make contact with one another along their medial parts [4715]. Embryologically, these structures arise together as an aggregation of cells readily observed at Carnegie stage 15 (CS15), and are referred to as the trapezius/SCM muscle complex.…”
Section: Discussionmentioning
confidence: 99%
“…These variations include an abnormal origin or the partial or complete absence of the muscle. Mehra et al 10 reported a rare case of a dorsoscapular triangle, due to the bilateral and complete absence of the cervical part of the trapezius muscle. In this case, each side of the muscle was presented as a right angle triangle extending from the 5 th cervical vertebrae to the 10 th thoracic vertebrae.…”
Section: Anatomical Variations Of the Trapezius Muscle Reported By Thmentioning
confidence: 99%
“…10 In the case of the trapezius muscle, causes may be inflammatory, vascular, neuropathic and myopathic. The congenital absence of the trapezius muscle maybe part of a Poland syndrome or Klippel-Feil syndrome.…”
Section: Anatomical Variations Of the Trapezius Muscle Reported By Thmentioning
confidence: 99%